Piękno Miłosierdzia. Dramaturgiczne wizerunki Brata Alberta - Olszewska, Maria Jolanta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Brother Albert Chmielowski has become a hero of several important literary texts, including the hero of two dramas created almost at the same time – during World War II. These are Adam Bunsch’s Gołębie Brata Alberta (1943), (Polish edition 1947 Przyszedł na ziemię święty) and Karol Wojtyla Brat naszego Boga (1944-1950). Both Bunsch and Wojtyla are fascinated by the character of Brother Albert and his life. Bunsch writes his drama as a soldier, artist-painter, literary, and Wojtyla, the future pope, as a priest. In the drama by Bunsch we have shown the way of life choices of Adam Chmielowski, who is looking for his place in life. We first see him as an insurgent soldier from 1863, then as a painter, and finally as a religious servant to the poor. Bunsch’s drama is similar to realistic, moral or biographical dramas. The author did not introduce theological content into it, but he emphasized ethical issues. In Karol Wojtyla’s drama we have a different approach to the character of Brother Albert. This drama is based on the foundation of personalism. It stands the human being in the center with its mystery of existence to relation to God based on love. The plot becomes a pretext for reflection on Mercy, which is pure Beauty. The visualization of Mercy in the discussed play is a picture of Chmielowski Ecce homo. Drama by Wojtyła has a theological tone. His theater is a theater of words, thoughts and philosophical-vision. So, despite significant differences in the concept of theater and drama, both dramas are testimony to the role that Brother Albert played in the current world.